Pengaruh Pendidikan Kesehatan Galactogogue Daun Torbangun (Coleus Amboinicus L) Terhadap Self Efficacy Ibu Menyusui Di Klinik Pratama Amanda Gamping Sleman - Ratna Prahesti; Nur Rahmawati Sholihah (Journal of Health (JoH), 2020)
Breast milk is the first and major food for infants. Breast milk contains the most complete nutritional composition and is ideal for the growth and development of infants during the first 6 months. UNICEF (2011) stated that children who are not breastfed have a 25% higher risk of death due to diarrhea and four times greater risk of pneumonia. The purpose of this study was to determine the effect of health education of galactogogue torbangun leaves (Coleus amboinicus l) on the self-efficacy of third-trimester pregnant women at the Amanda Clinic, Gamping, Sleman, Yogyakarta. This study used a quasi-experimental design with experimental post-test group design, namely the treatment group and the control group. The study was conducted at the Amanda Clinic, Gamping, Sleman in July 2018 with total samples of 42 respondents by using a quota sampling technique. The results showed the differences in self-efficacy between before and after treatment of health education which shown from the paired t-test value (p = 0,000 <0.05% (95% CI).